2020
DOI: 10.1111/bjd.19041
|View full text |Cite
|
Sign up to set email alerts
|

No association between whole‐body ultraviolet A1 phototherapy and skin cancers in humans: a cancer registry linkage study

Abstract: adipogenic differentiation inducer, can affect the subcutaneous layer in human skin in vivo. Although we still do not know the exact roles of the aged subcutaneous layer, we believe that an understanding about this layer may provide us with new insights and strategies for skin antiageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…ultraviolet A1 (UVA1) phototherapy has a comparable efficacy in moderate-to-severe plaque-type psoriasis and could improve the clinical manifestations and quality of life more quickly than narrow band ultraviolet B therapy with no significant side effects, including lack of increased risk of cutaneous malignancies. 13,14 With the recent COVID-19 outbreak, dermatologists should prioritize and individualize treatment protocols to psoriatic patients based on diseases severity, patients medical conditions, and viral invasiveness. For biologics in the precoronavirus era, respiratory infection rates were comparable to placebo.…”
mentioning
confidence: 99%
“…ultraviolet A1 (UVA1) phototherapy has a comparable efficacy in moderate-to-severe plaque-type psoriasis and could improve the clinical manifestations and quality of life more quickly than narrow band ultraviolet B therapy with no significant side effects, including lack of increased risk of cutaneous malignancies. 13,14 With the recent COVID-19 outbreak, dermatologists should prioritize and individualize treatment protocols to psoriatic patients based on diseases severity, patients medical conditions, and viral invasiveness. For biologics in the precoronavirus era, respiratory infection rates were comparable to placebo.…”
mentioning
confidence: 99%
“…However, another study from Korea, which involved over 60,000 patients, found no overall increased risk of skin cancer, even with more than 500 narrowband UVB treatments in some cases, but it did find an increased risk of actinic keratoses 97 . Additionally, no clinically measurable increase in skin cancer associated with UVA1 therapy has been demonstrated 98 . Furthermore, it is also not clear whether therapeutically high cumulative doses of UVA or UVB increase the risk of melanoma.…”
Section: Physical Basicsmentioning
confidence: 99%
“…97 Additionally, no clinically measurable increase in skin cancer associated with UVA1 therapy has been demonstrated. 98 Furthermore, it is also not clear whether therapeutically high cumulative doses of UVA or UVB increase the risk of melanoma. Data from American publications indicate an increased risk of melanoma after PUVA treatment, but this may be partly due to the fact that American protocols include monthly PUVA maintenance treatments after achieving remission, 99 whereas European protocols do not include further irradiation after remission and do not show an increased risk of melanoma.…”
Section: Side Effects Of Phototherapymentioning
confidence: 99%
“…Eine weitere Studie aus Korea (> 60 000 Patienten) konnte aber auch bei teilweise über 500 Schmalband‐UVB‐Behandlungen kein allgemein erhöhtes Hautkrebsrisiko aber vermehrt aktinische Keratosen beobachten 97 . Auch für UVA1 ließ sich bisher keine klinisch messbare Zunahme von Hautkrebs nachweisen 98 . Nicht eindeutig ist ebenfalls, ob therapeutisch applizierte, hohe kumulative UVA‐ oder UVB‐Dosen das Melanomrisiko erhöhen.…”
Section: Introductionunclassified